NOTES ON EGGS, LARVA AND JUVENILES OF FISHES FROM INDIAN WATERS V. Euthynnus affinis (Can - Jones, S (Indian Journal of Fisheries, 2015)
Larval stages of Katsuwonus pelamis (Linnaeus) and Ncothutms mccropterus (Temminck and Schlegel) collected mostly en beard Ihe Research Vessel KALA VA from the Laccadive Sea and the Gulf of Marrar were described in the previous two numbers in this series (Jones, 1959). A few small larvas resembling those of Euthynnus described from the Pacific region by Wade (1951) and Matsumoto (1958 and 1959) were present in the KALAVA collection but the material was not adequate for fixing the identity with reasonable certainty. However, a fairly large number of juvenile and young stages of Euthynnus affinis were obtained from shore-seines from Vizhinjam, a fishing centre about 9 miles south of Trivandrum and from boat-seines from Calicut and these are dealt with in this account.